Mapping (but Not Solving) the Science Communication Crisis - Altbach, Phil; de Wit, Hans (International Higher Education, 2025)
<h3 id="the-dramatic-expansion-of-higher-education-and-research-has-meant-that-publications-have-expanded-exponentially-they-have-become-the-coin-of-the-realm-for-academic-advancement-university-prestige-and-global-rankings-new-technologies-multinational-publishers-and-open-access-arrangements-have-led-to-an-expansion-that-is-essentially-destroying-the-traditional-publishing-system-and-creating-an-insurmountable-crisis-in-scientific-communication-this-analysis-provides-a-roadmap-of-the-crisis-but-no-clear-solutions" data-pm-slice="1 1 []">The dramatic expansion of higher education and research has meant that publications have expanded exponentially. They have become the coin of the realm for academic advancement, university prestige, and global rankings. New technologies, multinational publishers, and open access arrangements have led to an expansion that is essentially destroying the traditional publishing system and creating an insurmountable crisis in scientific communication. This analysis provides a roadmap of the crisis, but no clear solutions.